2022
DOI: 10.4103/jehp.jehp_720_21
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of physical activity during COVID-19 pandemic among Indonesian young adults

Abstract: BACKGROUND: Social distancing policy during the COVID-19 pandemic may affect physical activity levels. This study aimed to compare physical activity levels before and during the pandemic and to explore physical activity correlates among Indonesian young adults. MATERIALS AND METHODS: This longitudinal study was conducted before the pandemic (n = 141) in September 2019 and was followed by an online follow-up survey during the pandemic (79% response rate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Moreover, we explored the associations between perceptions of the impact of COVID-19 on PA and other variables assessed at this time point, including leisure-time PA and related social cognitive theory (SCT) constructs (walking self-efficacy, social support, planning, goal setting, outcome expectations, and enjoyment, which are considered early indicators of behavior change). In line with previous research evaluating the relationship between SCT constructs and pandemic-era PA behavior [20], we hypothesized that perceptions of the impact of COVID-19 on PA would be negatively associated with leisure-time PA and SCT constructs; that is, individuals experiencing pandemic-related PA barriers may feel less confident (or self-efficacious) in their ability to be physically active, lack a supportive social network for staying active, find it difficult to maintain healthy self-regulation behaviors, etc. The results presented herein will help guide ongoing and future efforts to address rural health disparities and offset the disruption in daily PA routines caused by a public health crisis.…”
Section: Introductionsupporting
confidence: 84%
“…Moreover, we explored the associations between perceptions of the impact of COVID-19 on PA and other variables assessed at this time point, including leisure-time PA and related social cognitive theory (SCT) constructs (walking self-efficacy, social support, planning, goal setting, outcome expectations, and enjoyment, which are considered early indicators of behavior change). In line with previous research evaluating the relationship between SCT constructs and pandemic-era PA behavior [20], we hypothesized that perceptions of the impact of COVID-19 on PA would be negatively associated with leisure-time PA and SCT constructs; that is, individuals experiencing pandemic-related PA barriers may feel less confident (or self-efficacious) in their ability to be physically active, lack a supportive social network for staying active, find it difficult to maintain healthy self-regulation behaviors, etc. The results presented herein will help guide ongoing and future efforts to address rural health disparities and offset the disruption in daily PA routines caused by a public health crisis.…”
Section: Introductionsupporting
confidence: 84%
“…A study in Indonesian among young adults was revealed a significant decline in physical activity during the COVID-19 pandemic due to work. [ 40 ] Physical inactivity is also being called another pandemic for several years,[ 41 ] and it can be expected that people may be moving even less during the COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the COVID-19 pandemic, Indonesian people lack physical activities as reflected by the daily steps count, where Indonesian people recorded the least steps compared to people from other countries [38]. COVID-19 pandemic further exacerbated this issue [39]. Compared to healthy individuals, T2D spent less time and effort to exercise during the pandemic [40].…”
Section: Discussionmentioning
confidence: 99%